2022
DOI: 10.1098/rsif.2021.0820
|View full text |Cite|
|
Sign up to set email alerts
|

Dental cementum virtual histology of Neanderthal teeth from Krapina (Croatia, 130–120 kyr): an informed estimate of age, sex and adult stressors

Abstract: The evolution of modern human reproductive scheduling is an aspect of our life history that remains vastly uncomprehended. The present work aims to address this gap by validating a non-destructive cutting-edge methodology to infer adult life-history events on modern teeth with known life history and then applying it to fossil specimens. We use phase-contrast synchrotron X-ray microtomography to visualize the dental cementum of 21 specimens: nine contemporary humans; 10 Neanderthals from Krapina (Croatia, 130–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 66 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…Details regarding the methods are reported in the electronic supplementary material. Histological thin sections were prepared following a previously published protocol [11]. To be suitable for high-vacuum SEM imaging, sections were uniformly carbon-coated using a Denton Desk V (Denton Vacuum, Moorestown, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details regarding the methods are reported in the electronic supplementary material. Histological thin sections were prepared following a previously published protocol [11]. To be suitable for high-vacuum SEM imaging, sections were uniformly carbon-coated using a Denton Desk V (Denton Vacuum, Moorestown, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Intrinsic and extrinsic events leave a permanent record in all calcified tissues, which are formed according to an internal biological rhythm [7]. Events correlating with AGLs include: reproduction [8,9], weaning [10], menopause [11], changes in diet [12] and climate [13][14][15][16]. Within mammals, teeth are the recording structure of choice as they are not remodelled during life [17].…”
Section: Introductionmentioning
confidence: 99%
“…The data were extracted from Endnote software in ‘.txt’ format and manually edited to arrange the studies by techniques. In total, 31 terms were considered based on these studies [ 11 , 31 , 39 , 56 , 57 , 77 , 78 , 89 , 90 , 121 , 169 , 170 , 171 , 172 , 173 , 175 , 193 , 195 , 247 , 266 , 286 , 294 , 299 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 , 311 , 312 , 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 , 327 , 328 , 329 , 330 , ...…”
Section: Figurementioning
confidence: 99%
“…The data were extracted from Endnote software (Clarivate) in ‘.txt’ format and manually edited to match the reading format and correlation of words; for example, British spelling was applied when translating non-English titles and acronyms were generally written in full length. The minimum number of occurrences of a term was set to four, and in total 140 terms were used based on these studies [ 11 , 31 , 39 , 56 , 57 , 77 , 78 , 89 , 90 , 121 , 169 , 170 , 171 , 172 , 173 , 175 , 193 , 195 , 247 , 266 , 286 , 294 , 299 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 , 311 , 312 , 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 , 327 ,…”
Section: Figurementioning
confidence: 99%
“…These tissues act as recoding structures [ 1 ], keeping track of the physiological changes experienced by an organism in the form of accentuated growth lines and changes in elemental composition. A large body of work spanning several decades has shown that a variety of both intrinsic and extrinsic events, including birth [ 2 , 3 ], reproduction [ 4 ], weaning [ 5 ], menopause [ 6 ], illnesses [ 7 ], dietary changes [ 8 ] and climate variation [ 9 11 ], leave a permanent record in calcified tissues which is preserved even in fossil specimens [ 12 ]. The microstructural organization of teeth is not altered during life [ 13 ].…”
Section: Introductionmentioning
confidence: 99%